Avaliação dos efeitos do fator estimulador de colônias de granulócitos (G-CSF) sobre as alterações de função cardíaca induzidas por dieta hipergordurosa em camundongos C57Bl/6 - Daltro, Pamela Santana (2013)
Dietary habits composed of high levels of fat are a trigger for obesity. This pandemic is involved with the development of cardiovascular diseases, due to structural and hemodynamic changes in the heart. The G-CSF has emerged as a potential treatment for many degenerative diseases, emphasizing its beneficial effect on the structural and functional regeneration of the heart in ischemic cardiomyopathy and Chagas disease, with diminished inflammation and fibrosis, and improvement of cardiac impulse generation and conduction. We used C57BL / 6 mice fed a high-fat (HF) diet that developed obesity, hyperglycemia and glucose intolerance. The changes in cardiac function were assessed by electrocardiogram, echocardiogram and treadmill. The animals were divided into two groups: standard diet (n = 8) and HF diet (n = 16) to induce obesity. 37 weeks after HF protocol, the animals were divided into three groups: treated with G-CSF (n = 8) + standard diet, not treated with G-CSF (n = 8) + standard diet, and the third group with standard diet only (n = 8). Results showed that replacing the standard diet following HF diet was responsible for the return to baseline of anthropometric and biochemical values, which were significantly elevated. Diet replacement alone did not reverse exercise intolerance or prevent cardiac abnormalities, such as bradycardia and increases in QRS amplitude, septal wall thickness and left ventricular posterior thickness. Diet replacement and treatment with G-CSF reversed structural changes in the heart and recovery of physical capacity.